2020
DOI: 10.15252/embj.2020105513
|View full text |Cite
|
Sign up to set email alerts
|

GSK3α, not GSK3β, drives hippocampal NMDAR‐dependent LTD via tau‐mediated spine anchoring

Abstract: Glycogen synthase kinase‐3 (GSK3) is an important signalling protein in the brain and modulates different forms of synaptic plasticity. Neuronal functions of GSK3 are typically attributed to one of its two isoforms, GSK3β, simply because of its prevalent expression in the brain. Consequently, the importance of isoform‐specific functions of GSK3 in synaptic plasticity has not been fully explored. We now directly address this question for NMDA receptor‐dependent long‐term depression (LTD) in the hippocampus. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 80 publications
(109 reference statements)
2
13
0
Order By: Relevance
“…In this study, the effect of irresponsive synapses may be related to synaptic shrinkage, as it has been reported that GSK3α, but not GSK3β, affected synaptic plasticity by regulating actin polymerization after chemical-LTD (chLTD) in DIV18 hippocampal neurons [68]. Additional evidence supporting the dominant role of GSK3α in LTD was recently found by Draffin et al [69], who revealed that GSK3α was required to induce LTD in hippocampal neuronal cells. Interestingly, during LTD, GSK3α was anchored to the dendritic spines via tau, which suggests that GSK3α/tau axis malfunction is a relevant step in tau-related pathologies.…”
Section: Gsk3α In Alzheimer's Disease and Neurodegenerative Disorderssupporting
confidence: 64%
“…In this study, the effect of irresponsive synapses may be related to synaptic shrinkage, as it has been reported that GSK3α, but not GSK3β, affected synaptic plasticity by regulating actin polymerization after chemical-LTD (chLTD) in DIV18 hippocampal neurons [68]. Additional evidence supporting the dominant role of GSK3α in LTD was recently found by Draffin et al [69], who revealed that GSK3α was required to induce LTD in hippocampal neuronal cells. Interestingly, during LTD, GSK3α was anchored to the dendritic spines via tau, which suggests that GSK3α/tau axis malfunction is a relevant step in tau-related pathologies.…”
Section: Gsk3α In Alzheimer's Disease and Neurodegenerative Disorderssupporting
confidence: 64%
“…Subsequent studies have identified downstream effectors of GSK-3β in LTD, such as PSD-95 (Nelson et al, 2013). However, other more recent work has favored GSK-3α as the paralog responsible for LTD (Shahab et al, 2014;Cymerman et al, 2015;Draffin et al, 2021) or has identified roles for both enzymes (McCamphill et al, 2020). Further studies that, for example, combine pharmacological agents with KO mice will be useful in establishing the relative roles of GSK-3α and GSK-3β in both synaptic plasticity and cognition.…”
Section: Effects Of Ct99021 On Synaptic Functionmentioning
confidence: 99%
“…This effect was highly specific for NMDAR-LTD since the same inhibitors had no effect on basal synaptic transmission, LTP, depotentiation or metabotropic glutamate receptor (mGluR-) LTD. Considerable evidence has since accumulated suggesting that GSK-3 is a pivotal kinase regulating the balance between LTP and LTD (Dewachter et al, 2009;Bradley et al, 2012;Besing et al, 2017;Draffin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although involved in common functions, GSK3α and GSK3β have non-overlapping functions best exemplified by the finding that knockout of GSK3β in mice generally results in embryonic lethality whereas global knockout of GSK3α results in viable animals although these mice develop age-related pathologies and a slightly shortened lifespan [ 116 , 117 , 118 ]. Specific non-overlapping functions for the two GSK isoforms in the brain have been described [ 119 , 120 , 121 , 122 ]. GSK3 is unusual among protein kinases in that it is generally constitutively-active making its inhibition, rather than activation, the primary mode of its regulation [ 123 ].…”
Section: The Enzymesmentioning
confidence: 99%